The benefits of adopting International Financial Reporting Standards: auditors' perception. (2nd March 2023) - Elhaj, Malik R.; Soliman, Maged
The aim of this study is to examine auditors' perceptions on the implementation of the International Financial Reporting Standards (IFRS). Selected experimental studies that focus on the IFRS adoption are analysed toward identifying a point reference that may cut across previous research and informing the development of the current research. Survey questionnaire is used with an open-ended question to supplement the quantitative component of the study. For the quantitative component, the Statistical Package for Social Sciences (SPSS) has been utilised and a qualitative data analysis software package (NVivo) is used to analyse qualitative data collected from the open-ended question. The findings indicate that auditors support the adoption of IFRS. In addition, participants perceived IFRS adoption to have increased financial reporting transparency, quality and comparability. Moreover, the auditors highlight the importance of training for both auditors and accountants on the implementation of IFRS to ensure effective integration of the accounting standards.